2005
DOI: 10.1177/107602960501100303
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Measurement of Reticulated Platelets for Diagnosis of Idiopathic Thrombocytopenic Purpura

Abstract: Reticulated platelets (RP) and large platelets (LP) were measured by an automated hematology analyzer (modified R-2000) in 287 healthy volunteers and 131 patients with thrombocytopenia or thrombocytosis. RP was significantly higher in patients with idiopathic thrombocytopenic purpura (ITP), especially in active phase, while RP was markedly lower in patients with essential thrombocytosis (ET) or chronic myelocytic leukemia (CML). LP was significantly higher in patients with ITP, especially in active phase, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…, 2002] and detectable by flow cytometry on the basis of their RNA content by means of staining with dyes such as Thiazole Orange. Consequently, reticulated platelet analysis has been proposed as a useful indicator of thrombopoiesis [Sakakura et al. , 2005] although this study also demonstrated that similar insights could be obtained with CD‐Sapphire MPV values.…”
Section: Discussionsupporting
confidence: 64%
“…, 2002] and detectable by flow cytometry on the basis of their RNA content by means of staining with dyes such as Thiazole Orange. Consequently, reticulated platelet analysis has been proposed as a useful indicator of thrombopoiesis [Sakakura et al. , 2005] although this study also demonstrated that similar insights could be obtained with CD‐Sapphire MPV values.…”
Section: Discussionsupporting
confidence: 64%
“…14,45 RP quantification is achieved using an RNA-specific vital dye (thiazole orange) that does not distinguish between ribosomal and mRNA. 10 We did not quantify RP percentage in this study, although such information has been previously reported, 14,46 with evidence that thrombocytosis patients had RP percentages that were similar to those of normal controls and not different between RT and ET patients. Increased relative and absolute RP counts were primarily restricted to the subset of thrombocytotic patients with concomitant thromboses.…”
Section: Discussionmentioning
confidence: 82%
“…If during the course of treatment or monitoring atypical features develop-for example, abnormalities in the white blood cell count, lymphadenopathy, multiple cytopenias-then the diagnosis of ITP should be reassessed. As in childhood ITP, we found insufficient evidence to recommend or suggest the routine use of antiplatelet, [61][62][63][64][65][66][67][68][69][70][71] antiphospholipid [72][73][74][75] and antinuclear antibodies, 13,76 thrombopoietin levels, 64,65,77 or platelet parameters obtained on automated analyzers 64,65,[78][79][80][81][82][83][84] in the evaluation of patients with suspected ITP.…”
Section: Question: What Testing Is Required To Confirm the Diagnosis mentioning
confidence: 99%